The political constraints for civil service reform in Georgia: history, current affairs, prospects and challenges. Issue 3 (2nd September 2019) - Kvashilava, Bakur
ABSTRACT: This study provides an examination (and an evaluation) of the reforms of the civil service of Georgia since its independence. These are divided into five distinct periods. The first one encompasses the time immediately after independence until the adoption of the Law on Civil Service in 1997. The second lasts until the end of the President Shevardnadze's government as a result of the Rose Revolution in November 2003. The third period – until 2007 – marks important reforms that the new United National Movement (UNM) government was able to implement capitalizing on overwhelming public support it enjoyed. From the second half of 2007 to 2012, the fourth period, the UNM government's pace of reforms significantly decreased, and even stalled in some areas. The last, fifth period, starts from the end of 2012 and continues to this day. That is when the Georgian Dream Coalition (GD) won the Parliamentary Elections. In the fifth and last period the government showed a clear preference for an independent, Weberian civil service as opposed to New Public Management (NPM) principles preferred by the UNM in their most decisive reforms. Success of reforms irrespective of the type of civil service preferred seems to be highly dependent upon political will and favourable political context.